2008
DOI: 10.1679/aohc.71.303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a weight compression and a magnet compression for experimental pressure ulcers in the rat. Histological studies and effects of anesthesia

Abstract: and low in the skin. The compression with anesthesia produced significantly milder injuries than those under anesthesia. These findings indicate that the difference in the extent of injuries between the weight compression and maget compression models are clearly attributable to the pentobarbital anesthesia induced during the compression. Results therefore show that experimental pressure ulcers should be examined in a waking condition and that magnet compression is a useful model for studying the pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…29) It has also been suggested that a copy number variation in a certain region of the genome may play a role as a genetic risk factor for iNPH. 19) Each hypothesis described above does not exclude the others; one hypothesis may focus on the etiology and pathogenesis of iNPH from a single viewpoint, differently from the others. Further study is needed to clarify the exact etiology and pathogenesis of iNPH.…”
Section: -B Etiologymentioning
confidence: 99%
See 4 more Smart Citations
“…29) It has also been suggested that a copy number variation in a certain region of the genome may play a role as a genetic risk factor for iNPH. 19) Each hypothesis described above does not exclude the others; one hypothesis may focus on the etiology and pathogenesis of iNPH from a single viewpoint, differently from the others. Further study is needed to clarify the exact etiology and pathogenesis of iNPH.…”
Section: -B Etiologymentioning
confidence: 99%
“…3,19,30,45,91,98,106,133) Memory is frequently impaired in patients with mild iNPH; however, recognition memory is relatively preserved compared with recall. 102) Verbal fluency is also impaired.…”
Section: -B Characteristics Of Cognitive Impairment (Dementia)mentioning
confidence: 99%
See 3 more Smart Citations